ABORTION AS A CAUSE OF DEATH MATERNAL - Maradiegue, Eduardo (2015)
The author defines abortion as a controverted pathology due to the various non-biologic components. It has been used since remote times as a resource to regulate fecundity. But the serious complications are still important causes of maternal death, generally as a consequence of severe infection. More than 400 000 induced abortions have been indirectly estimated in Peru, responsible for an important number of deaths due to this cause. Main non-mortal complications of induced abortion are chronic pelvic pain, ectopic pregnancy, sterility and premature menopause due to oophorectomy. The severity of infection in induced abortion done in adverse conditions frequently causes multiple organic compromise, its therapy depending in the pregnant woman’s health and in the severity of the bacteria or bacteriae involved. Once septic abortion is diagnosed treatment should be in a hospital with resolution capacity, as late or inappropriate treatments can derive in septic shock with high probabilities of maternal death (20 to 50%). Consider infection is polymicrobial and requires intensive and wide spectrum antibiotics. Use intravenous therapy with ampicillin + gentamicin + chloramphenicol or metronidazole; the scheme may vary though depending on drug disposition. The antibiotic therapy has to be maintained until two days after fever disappears, with no need to continue with oral therapy. Aside from the antibiotic therapy, uterus has to be evacuated as soon as possible, either by curettage or hysterectomy, depending on the clinical status.